Kajian Potensi Hutan Mangrove Untuk Pembangunan Ekowisata Di Kelurahan Belawan Sicanang Kecamatan Medan Belawan Provinsi Sumatera Utara “Study of mangrove forest potential for ecotourism development at belawansicanang village, medanbelawan sub district of - M Ripal Al-kautsar; Pindi Patana; Irwanmay Irwanmay (Program Studi Manajemen Sumberdaya Perairan, Fakultas Pertanian Universitas Sumatera Utara, 2017)
Researchonthe tourism potentialof mangrovesat Kelurahan Belawan Sicanang village in Medan Belawan districtneeds to be donetodevelopthe areaofeco-tourismaspect. The purpose ofthis research was todeterminethe potential andcondition of the resourcethatcan be performed onthe mangrove ecosystemin Kelurahan Belawan Sicanang village andassess the appropriateness andthe carrying capacity ofmangrove ecosystemsfor the management ofmangroveecotourismin Kelurahan Belawan Sicanang village. Based on research, the mangrove ecosystem in Kelurahan Belawan Sicanang village consisted by nine speciesof mangrove, whichAcrotichum specium, Avicennia alba, Avicennia marina, bruguiera sexangula, Excoecaria agollocha, Lumnitzera littorea, Rhizopora stylosa, Soneratia caseolaris, Soneratia ovata.Generally, the density valuemost speciesof great valueisthe typeExocoecaria agollocha.The suitability index of mangrove ecosystem included into the category corresponding conditional (SB).There are two proposed location tracks, that waters track and the inlands track. The value of the region carrying capacity of water track is 160 people per day and a land track is 180 people per day.Keywords : Ecotourism, Mangrove, Belawan Sicanang